Radio over fiber broadband access networks architectures based on wavelength division multiplexing techniques - Avó, R. (2013)
The recent remarkable growth in bandwidth of both wired optical and wireless access networks supports a burst of new high bandwidth Internet applications such as: peer-topeer file sharing, cloud storage, on-line gaming, video streaming, etc. Within this scenario, the convergence of fixed and wireless access networks offers significant opportunities for network operators to satisfy user demands, and simultaneously reduce the cost of implementing and running separated wireless and wired networks. The integration of wired and wireless network can be accomplished within several scenarios and at several levels. In this thesis we will focus on converged radio over fiber architectures, particularly on two application scenarios: converged optical 60 GHz wireless networks and wireless overlay backhauling over bidirectional colorless wavelength division multiplexing passive optical networks (WDM-PONs). In the first application scenario, optical 60 GHz signal generation using external modulation of an optical carrier by means of lithium niobate (LiNbO3) Mach- Zehnder modulators (MZM) is considered. The performance of different optical modulation techniques, robust against fiber dispersion is assessed and dispersion mitigation strategies are identified. The study is extended to 60 GHz carriers digitally modulated with data and to systems employing subcarrier multiplexed (SCM) mm-wave channels. In the second application scenario, the performance of WDM-PONs employing reflective semiconductor optical amplifiers (RSOAs), transmitting an overlay orthogonal frequency-division multiplexing (OFDM) wireless signal is assessed analytically and experimentally, with the relevant system impairments being identified. It is demonstrated that the intermodulation due to the beating of the baseband signal and wireless signal at the receiver can seriously impair the wireless channel. Performance degradation of the wireless channel caused by the RSOA gain modulation owing to the downstream baseband data is also assessed, and system design guidelines are provided.